The importance of the language used in substance use and addiction - Demirbaş, Hatice (Journal of Dependence, 2020)
The language used is important when it comes to substance use. When substance abuse is used, terms such as alcohol abuse, alcoholic, addict, substance addict, and junkie are used. These terms may adversely affect the way society perceives substance abuse, attitudes of healthcare workers, legal processes and affected people. Stigmatization is the biggest obstacle for addiction treatment. For the reasons stated above, in terms of substance use, the terms free of stigmatization should be used both in the literature and in communication with patients and in reports and diagnoses. In addition, the language used should encourage the healing process and be free from slang and similar phrases. Improper use of language requires defining the term for improvement. The language defined by the biopsychosocial model, including a comprehensive medical model, should be used in substance use and language relations. Different approaches need to be adopted to reduce stigmatization underlying differences in public beliefs and attitudes related to drug addiction and to develop appropriate policies. Substance abuse and similar terms should not be used among professionals or community.
Keywords: Language; substance use; stigmatization; addiction